2010
DOI: 10.5015/utmj.v88i1.1283
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Depression and Anxiety Symptoms among Hospitalized Geriatric Medical Inpatients: A study from a Tertiary Level Hospital in Nepal

Abstract: ABSTRACT Introduction: Depression and Anxiety symptoms are widely prevalent in the geriatric population and the prevalence is higher in those suffering from any kind of medical illness. Although the prevalence of anxiety and depression among elderly medical patients have been evaluated in a few studies from developed countries in Europe and the Americas, data from a developing country like Nepal is lacking. The main aim of our study was to estimate the burden of these psychiatric morbidities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The minimum age was 60 years and maximum was 89 years. Our findings correspond to the findings of earlier study in Nepal, which shows that mean age of the patients was 69.4 ± 4.3 years 4 and to the finding of study of Pereira YDS et al in which 70% of the sample were of age group 60-69 years, with mean age of 65.8 ± 6.11 years. 5 Our finding is in accordance to study by Singh GP et al 6 which showed age group 60 -65 years had highest proportion (56.9%) followed by 66-70 years (19.34%).…”
Section: Socio-demographic Profile: Age and Sex Distributionsupporting
confidence: 82%
See 1 more Smart Citation
“…The minimum age was 60 years and maximum was 89 years. Our findings correspond to the findings of earlier study in Nepal, which shows that mean age of the patients was 69.4 ± 4.3 years 4 and to the finding of study of Pereira YDS et al in which 70% of the sample were of age group 60-69 years, with mean age of 65.8 ± 6.11 years. 5 Our finding is in accordance to study by Singh GP et al 6 which showed age group 60 -65 years had highest proportion (56.9%) followed by 66-70 years (19.34%).…”
Section: Socio-demographic Profile: Age and Sex Distributionsupporting
confidence: 82%
“…9 A study conducted in TUTH in 2009 among 42 geriatric inpatients showed higher prevalence of anxiety symptoms (76.1%). 4 This significantly high prevalence was seen probably because the study population was the geriatric patients admitted with medical illness, which might be the stressor to them. Finding of our study is consistent with the finding of study done by Singh GP et al which showed Neurotic, stress related and somatoform disorders (15.47%) as second commonest illness.…”
Section: Psychiatric Morbiditiesmentioning
confidence: 99%
“…5 Similarly another study from a tertiary level hospital in Nepal conducted among hospitalized geriatric medical inpatients concluded that 57.1% of hospitalized geriatric patient had depressive symptoms and 17.3% of healthy community dwelling had depression. 8 A study conducted on prevalence of depression among institutionalized elders in Colombo showed 56% of population had depression. 7 Study conducted on community dwelling areas of West Bengal showed 53.7% depression.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies are Epidemiological field surveys [2][3][4][5] , hospital based outpatient studies [6][7][8][9] as well as inpatient studies [10][11][12] . In the present decade there is resurgence of geropsychiatric study reports from Nepal [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%